CP-123 Improving access to mental health services: a new pharmacy role in general hospital psychiatry liaison. (24th March 2015) - Brooks, J; Schneider, C; Hashmi, M; Hebron, B; Wilson, K
Abstract : Background: When mentally ill patients are admitted to general hospitals, effective psychiatry liaison results in better patient outcomes and reduced length of stay. 1 However, studies in our institution suggest that routine referrals can take 14 days from hospital admission, and only occur in a third of patients taking drugs for mental health conditions. 2 Purpose: To determine if a novel, pharmacist-driven, referral pathway can improve patient access and reduce the time delay associated with referrals. Material and methods: A pharmacist referral system using real-time dispensing information and direct reports from ward pharmacy teams was developed to identify hospital in-patients receiving antipsychotics, mood stabilisers or dementia medicines. A specialist pharmacist reviewed the patient and referred him/her to psychiatric liaison services if indicated. Data were recorded in line with national [Caldicott] ethical guidelines. Results: Between 17/09/2012 and 28/10/2013 the pharmacist made 41 referrals to psychiatric liaison services, accounting for 45% of the total number of referrals in this patient cohort. The mean time from hospital admission to pharmacist referral was 4.4 days (107 h, SD: 110 h). Increased access to psychiatric services was also seen with 47% (n = 138) patients being referred representing a 14% absolute increase from baseline. Conclusion: A specialist pharmacist linking acute and psychiatric services in an acute, general hospital improves access and reduces delays from admission to psychiatric expertise. References and/or Acknowledgements: Mental Health Network NHS Confederation. With money in mind: The benefits of liaison psychiatry. Briefing 2011 Schneider C, et al . Using hospital pharmacy dispensing records to categorise referrals to the RAID service: a preliminary study. IJPP 2012;20:35 No conflict of interest.